2009
DOI: 10.1063/1.3040321
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and high thermoelectric efficiency of Zintl phase YbCd2−xZnxSb2

Abstract: We synthesized a series of polycrystalline YbCd2−xZnxSb2 (x=0, 0.4, 0.8, 1, 1.2, 1.6, and 2) samples and measured their thermoelectric properties. Thermoelectric figure of merit ZT at 700K is higher than 1.0 for Cd-rich samples (x=0, 0.4, 0.8, and 1.0) and Zn substitute of Cd in YbCd2Sb2 can easily tune carrier concentration and reduce thermal conductivity. When x=0.4, sample exhibits the highest power factor (12–20μWcm−1K−2), the lowest lattice thermal conductivity (1.0Wm−1K−1 at 300K), highest ZT (1.2 at 700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 14 publications
(6 reference statements)
6
149
1
Order By: Relevance
“…8A). Such a ZT value is competitive with the reported Sb-based p-type Zintl phases (22,26,27,50) and even other good p-type skutterudites (51) and half-Heuslers (52) in this temperature range (Fig. 8B).…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…8A). Such a ZT value is competitive with the reported Sb-based p-type Zintl phases (22,26,27,50) and even other good p-type skutterudites (51) and half-Heuslers (52) in this temperature range (Fig. 8B).…”
Section: Methodsmentioning
confidence: 60%
“…Remarkable achievements have been reported with maximal ZT around or more than 1, e.g., β-Zn 4 Sb 3 (20,21), Yb 14 Mn 1−x Al x Sb 11 (22,23), and A y Mo 3 Sb 7-x Te x (24). In particular, Zintl phases AB 2 Sb 2 (A = Ca, Yb, Eu, Sr; B = Zn, Mn, Cd, Mg) (25)(26)(27)(28)(29) crystallizing in CaAl 2 Si 2 structure have been extensively studied with the highest ZT for YbZn 0.4 Cd 1.6 Sb 2 ∼ 1.2 at 700 K. The A sites of these materials have been shown to contain exclusively divalent ions, which are limited to alkalineearth-based and rare-earth-based elements like Eu and Yb, whereas B is a d 0 , d 5 , d 10 transition metal or a main-group element like Mg 2+ (30,31). Despite the extensive research on Zintl antimonides, analogous Bi-based Zintl materials have received little attention, even given the competitive TE performance of this system.…”
mentioning
confidence: 99%
“…Besides the filled skutterudites and diamond-like compounds, many Zintl compounds are another type of structure with a well-defined conductive network, in this case composed of the polyanion sublattice. [75][76][77][78] Theoretical description of electrical transport and challenges So far, we have reviewed three topics concerning the electrical transport: band engineering; scattering engineering; and conductive networks in complex compounds. The first two are primarily aimed at the power-factor enhancement by the manipulations on either the band structure or the carrier scattering.…”
Section: Manipulation Of Carrier Scatteringmentioning
confidence: 99%
“…16 and 18) and YbCd 2Àx Zn x Sb 2 , both of which have zT values above unity at high temperatures. 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Recently, Yb 9 Mn 4.2 Sb 9 was shown to have promising thermoelectric performance (zT ¼ 0.7 at 950 K) by Bux et al 17 The structure of Yb 9 M 4+x Sb 9 is shown in Fig. 1, where M can be Fig.…”
Section: Introductionmentioning
confidence: 99%